1997
DOI: 10.1093/milmed/162.4.249
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea-Hypopnea Syndrome in a Sample of Veterans of the Persian Gulf War

Abstract: The prevalence of sleep apnea-hypopnea syndrome (SAHS) was investigated in a selected group of veterans of the Persian Gulf War at Brooke Army Medical Center. One hundred ninety-two self-referred patients participated in the full evaluation of the Comprehensive Clinical Evaluation Program (CCEP) for veterans of the Persian Gulf War. After completing an initial survey, an interview and examination were performed by staff internists. Forty-six participants with histories suggestive of a sleep disorder were refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…Hence, our data support a psychomotor-related dysfunction rather than fine motor coordination problems, observations that are similar to that reported for another organophosphate AChE inhibitor pesticide, diisopropylfluorophosphate (Terry et al 2011). It is also possible that these GW-agent-induced neurobehavioral changes may be a consequence of circadian abnormalities, often reported by veterans with GWI (Haley et al 2004;Peacock et al 1997), and as such, likely to be a consequence of GW agent exposure. Nevertheless, the observed delayed presentation of neurobehavioral symptoms in GW agent-exposed mice is consistent with the observation of delayed manifestation of GWI in veterans, where 60% of GWI symptoms developed once veterans returned from the war, and 40% of the symptoms emerged years later (Kroenke et al 1998).…”
Section: Discussionsupporting
confidence: 89%
“…Hence, our data support a psychomotor-related dysfunction rather than fine motor coordination problems, observations that are similar to that reported for another organophosphate AChE inhibitor pesticide, diisopropylfluorophosphate (Terry et al 2011). It is also possible that these GW-agent-induced neurobehavioral changes may be a consequence of circadian abnormalities, often reported by veterans with GWI (Haley et al 2004;Peacock et al 1997), and as such, likely to be a consequence of GW agent exposure. Nevertheless, the observed delayed presentation of neurobehavioral symptoms in GW agent-exposed mice is consistent with the observation of delayed manifestation of GWI in veterans, where 60% of GWI symptoms developed once veterans returned from the war, and 40% of the symptoms emerged years later (Kroenke et al 1998).…”
Section: Discussionsupporting
confidence: 89%
“…Prevalence rates for OSA are consistent with a younger sample of Gulf War 1 veterans [29]. Higher BMI, in combination with higher rates of diabetes and sleep symptoms, are consistent with comorbid sleep conditions that suggest poorer health outcome and quality of life noted in studies of civilians with OSA [1,2,4,9,32,33].…”
Section: Discussionsupporting
confidence: 68%
“…Nevertheless, associations between OSA and CVD in this relatively small sample are consistent with large national studies [15][16][17][18]. Furthermore, we acknowledge that we cannot rule out preferential participation of subjects with ischemia given that this study was advertised as "diet and stroke risk"; however, it is unlikely that participants self-selected based on OSA because the study was not advertised as such, and prevalence rates of OSA in this study are similar to other military veterans [29]. Minority groups other than Mexican-Americans were not recruited for this study, in part, because of the Vascular Center focus on Mexican-American-Hispanics, the largest minority group in the southwest desert.…”
Section: Limitationssupporting
confidence: 75%
See 1 more Smart Citation
“…Peacock et al 6 reported sleep apnea-hypopnea syndrome in 8% of the participants of a Comprehensive Clinical Evaluation Program for GW veterans at Brooke Army Medical Center in Texas. Although 8% is slightly higher than the estimated prevalence of OSA in the general adult male population (3–7%), 7 another study failed to find evidence of increased sleep apnea in 22 ill GW veterans compared to 19 matched control GW veterans.…”
Section: Introductionmentioning
confidence: 99%